Determination of lamotrigine in human plasma and saliva using microextraction by packed sorbent and high performance liquid chromatography–diode array detection: An innovative bioanalytical tool for therapeutic drug monitoring - Ventura, Sandra (2016)
A ground-breaking high-performance liquid chromatography-diode array detection method based on microextraction by packed sorbent (MEPS) as sample preparation approach is described herein for determination of lamotrigine (LTG), a narrow therapeutic index drug, in human plasma and saliva. MEPS variables and chromatographic conditions were optimized to achieve appropriate selectivity and sensitivity using small sample volumes (100 μL). The chromatographic separation of LTG and chloramphenicol [internal standard (IS)] was accomplished in < 5 min on a C18-column, at 35 °C, using a mobile phase composed by acetonitrile/methanol/water-triethylamine 0.3% at pH 6.0 (13:13:74, v/v/v) pumped isocratically at 1 mL/min. LTG and IS were detected at 215 nm. A good linearity was obtained for LTG (r² ≥ 0.9936) in the range of 0.1–20 μg/mL in plasma and saliva, with the limit of quantification of 0.1 μg/mL. The method was shown to be precise (RSD ≤ 14.5%) and accurate (bias ± 13.4%), and the absolute recovery ranged from 64.9% to 73.6%. The stability of LTG was demonstrated in plasma and saliva samples in all studied conditions. The proposed assay was applied to the analysis of real human plasma and saliva samples from epilepsy patients under LTG therapy and the results support its usefulness for therapeutic drug monitoring.